2015
DOI: 10.1007/s11998-014-9633-4
|View full text |Cite
|
Sign up to set email alerts
|

Tungstate and vanadate-doped polypyrrole/aluminum flake composite coatings for the corrosion protection of aluminum 2024-T3

Abstract: Polypyrrole (PPy) doped with either tungstate or vanadate as counter anions was synthesized by chemical oxidative polymerization on the surface of aluminum (Al) flakes. This resulted in the deposition of PPy on the surface of the Al flakes leading to the formation of doped PPy/Al flake composite pigments. These composite pigments were characterized by Fourier transform infrared spectroscopy, scanning electron microscopy, energy dispersive spectroscopy, conductive-atomic force microscopy, four-point probe condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Bands at 801 cm −1 are due to the stretching vibration of V=O in the remaining V2O5 in the composite product. The peak of 560 cm −1 is due to the vanadate ion bond in the composites [27]. The SEM and EDX experiments confirmed that the synthesized product is a composite containing PPy and V2O5.…”
Section: Ftir Spectroscopic Analysismentioning
confidence: 61%
See 1 more Smart Citation
“…Bands at 801 cm −1 are due to the stretching vibration of V=O in the remaining V2O5 in the composite product. The peak of 560 cm −1 is due to the vanadate ion bond in the composites [27]. The SEM and EDX experiments confirmed that the synthesized product is a composite containing PPy and V2O5.…”
Section: Ftir Spectroscopic Analysismentioning
confidence: 61%
“…Jadhav [27] reported a PPy coating doped with vanadate and tungstate. With the degradation of PPy in the composite coating, the doped anions were released along with it, becoming a corrosion inhibitor in the system and slowing the corrosion of the aluminum substrate.…”
Section: Conductivitymentioning
confidence: 99%
“…Tungstate has a structure almost similar to molybdenum, but like molybdate cannot withstand electrochemical corrosion. According to [ 35 ], the presence of tungstate as impurities in poly(pyrrole) prevents the polymer defect and, to some extent, increases the corrosion resistance. However, after adding samarium tungstate nanoparticles to the pyrrole solution during electro-polymerization, the results were not as favorable as for SmM NPs@PP/GCE.…”
Section: Resultsmentioning
confidence: 99%
“…The surfactant and oxidizing agent increased the conductivity and yield of polypyrrole [ 41 ]. Polypyrrole doped with tungstate or vanadate was synthesized by the chemical polymerization method and characterized by various techniques [ 42 ].…”
Section: Synthesis Of Conducting Polymersmentioning
confidence: 99%
“…Fillers also play a pivotal role towards modification in the semiconducting and electrochemical performance of CPs. Since past decades, a wide range of chalcogenides derived from transition metals has been employed as fillers for modification in semiconducting [ 2 ] and electrochemical performance of CPs [ 3 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], as illustrated in Table 1 . The product derived through the blending of such fillers with CPs is defined as PNCs.…”
Section: Introductionmentioning
confidence: 99%